Sektor Pariwisata di Kabupaten Sleman Pada Masa Pandemi COVID-19 - Jihan Nisrina Irawati; Maya Damayanti (Jurusan Perencanaan Wilayah dan Kota, 2023)
Tourism is one of the most affected sectors due to the spread of COVID-19 Virus. The result of the spread of this virus in tourism sectors are economy loss and a decrease in tourist arrivals. Besides that, COVID-19 Virus also has caused prefence change in terms of choosing destinations. That problem will impact the process of tourism’s recovery after the Pandemic COVID-19 globally and even locally. Therefore, it is necessary to conduct a research that will give a picture of tourism sector during Pandemic COVID-19. This research was conducted in Kabupaten Sleman, one of regencies in Daerah Istimewa Yogtakarta which highly depends on tourism in its economy. This research aims to determine a picture of tourism sector in Kabupaten Sleman during Pandemic COVID-19. The results of this research are Pandmic COVID-19 has impacted on tourism in Kabupaten Sleman economically and a tourism preference change. The conclusion of this research is Kabupaten Sleman experienced economy loss and a decrease in tourist arrivals. Besides that, nature tourism has became the most visited destinations in Kabupaten Sleman during Pandemic COVID-19.